Negative frequency-dependent selection through variations in seedling fitness due to genetic differentiation of parents’ pair in a tropical rainforest tree, Rubroshorea curtisii (Dipterocarpaceae) - Tani, Naoki; Ng, Chin Hong; Lee, Soon Leong; Lee, Chai Ting; Muhammad, Norwati; Kondo, Toshiaki; Tsumura, Yoshihiko; Sugiyama, Saori; Niiyama, Kaoru; Ripin, Azizi; Kassim, Abdul Rahman; Musa, Samsudin (Frontiers in Genetics, 2025)
IntroductionThe role of syngameons in adaption to microgeographical environmental heterogeneity is important and could be one of the sources of rich species diversity in tropical forests. In addition, negative frequency- or density-dependent selection is one of the major processes contributing to the maintenance of genetic diversity.MethodsTo assess genetic factors that affect the fitness of seedlings of Rubroshorea curtisii, a dominant canopy tree species in hill dipterocarp forests, the inter- and intra-population genetic structure of individuals from natural populations and individuals at two permanent plots in a hill dipterocarp forest with reproductive stage was studied. Further, a total of 460 seedlings derived from six mother trees in the plot were raised in a nursery, and their pollen donors were identified using genetic marker based paternity assignment. Seed weight, bi-parental genetic relatedness, and bi-parental genetic heterogeneity based on the clustering analysis were used to analyze their effects on seedling fitness.ResultsA Bayesian based clustering analysis revealed that three genetically distinct clusters were observed in almost all populations throughout the distributional range of the species in Malay Peninsula and provided the optimum explanation for the genetic structure of 182 mature individuals in the plots. The two clusters showed larger genetic differentiation from the ancestral admixture population, but the other one was not differentiated. The bi-parental larger genetic heterogeneity was associated with a significantly higher probability of seedling survivorship, and likewise, higher performance of vertical growth of the seedlings; but the seed weight and genetic relatedness did not significantly affect those.DiscussionThis evidence suggests that fitter seedlings derived from mating between parents with different genetic clusters contribute to maintaining genetic diversity through negative frequency-dependent selection and may have an important role in adaptation in the tropical forest plant community.